Микроволновый нагрев: особенности модернизации технологии - Demyanchuk, B. А. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
Based on the analysis of traditional microwave heating technology for dielectric materials, a method and device for microwave heating in non-resonant chambers are proposed. Compared to conventional resonant systems, the new non-resonant heating systems are distinguished by the absence of local underheating and overheating zones, as well as background interference, and by the independence of chamber efficiency from the level of its loading. The principles of constructing new chambers, the physical essence of their functioning, advantages, and prospects for application are discussed.